KUALITAS APLIKASI, HARGA, DAN PERSAINGAN SEBAGAI DETERMINAN NIAT PAKAI ULANG APLIKASI PEMBAYARAN PPOB OLEH LOKET MITRA DI KOTA BANDUNG - Afwi Naufal Safawi; Agus Hasan Pura Anggawidjaja (Parahyangan Management Science and Practices Student Review, 2025)
This study examines the determinants of partner counters’ intention to reuse a PPOB (Payment Point Online Bank) digital payment application in Bandung, focusing on application quality, price, and competition. The research responds to a sustained downturn at the case firm (anonymised here as PT CAM) where registered partner counters in Bandung fell from 267 in 2020 to 128 in 2023, alongside declining transaction volumes. Using an explanatory quantitative design, primary data were gathered through a questionnaire administered to 113 partner counters selected by purposive sampling, and analysed with descriptive statistics and multiple linear regression. The results show that price and competition each exert a positive and significant effect on reuse intention, whereas application quality has no significant partial effect. Jointly, the three variables account for 32.9% of the variance in reuse intention, with price the strongest predictor. The findings indicate that, for agent-based payment platforms, a competitive and transparent fee structure matters more for partner retention than interface quality on its own. The firm is advised to rationalise its administrative fees, build a mobile-accessible application, and sharpen its competitive differentiation.